Konsep Deep Learning Sebagai Pilar Dalam Strategi Pendidikan Berkualitas - Kadarismanto; Kharisma Puspita Sari (https://journal.metanusantara.com/pedagogia, 2025)
The quality of education in the digital era demands a deeper and more adaptive learning approach. Deep learning as a learning strategy oriented towards conceptual understanding and critical thinking is a solution in improving the quality of education. This concept emphasises students' active involvement in the exploration, analysis, and application of knowledge in a real context. However, the implementation of this method in various educational institutions still faces challenges, especially in the readiness of educators and supporting infrastructure.This research uses a qualitative approach with a case study design to explore the application of deep learning in quality education strategies. The data sources consist of teachers, lecturers, and students who have direct experience in this method, selected through purposive sampling technique. Data were collected through in-depth interviews, participatory observation, and document analysis. Data were analysed using thematic analysis to identify patterns of implementation, impacts, and challenges in implementing deep learning. The results show thatdeep learning has a positive impact on students' conceptual understanding, critical thinking skills, and creativity. The implementation of this method through project-based learning (project-based learning) and inquiry-based approach is proven to increase students' active engagement. However, challenges such as educators' readiness and limited infrastructure are still the main obstacles. Therefore, a more systematic strategy is needed in integrating deep learning into the education system so that it can be implemented effectively.